Peran Gelombang Korea (Korean Wave) Terhadap Creative Business Masyarakat di Provinsi Jawa Timur - Shofwaties Anissa Lazzuarda (Jurnal Ilmu Ekonomi, 2022)
This study aims to find out the Role of the Korean Wave (Korean Wave) To Creative Business Community in East Java Province, and find out the formation of Creative Business from the influence of the Korean Wave (Korean Wave). This research was conducted on several creative business communities in East Java Province with a total sample of 31 respondents of creative businessmen based on purposive sampling techniques. The object in this study is a creative business formed from Korean waves such as K-POP (Korean Music), K-Fashion (Korean Fashion), and K-Food (Korean Food). Data collection in this study was collected through observation and interview with several stages of data analysis such as data collection, data reduction, presentation of data, and withdrawal of conclusions.  The results of this study concluded that the existence of the Korean Wave plays a role in creative business in East Java Province. This role has been the reason for the formation of various creative businesses.